Evaluasi Tingkat Kerusakan Jalan dengan Metode Bina Marga dan Pavement Condition Index pada Jalur Evakuasi di Kabupaten Aceh Barat - Hilma Erliana; Cut Liliiza Yusra; Ade Dwinta (Universitas Islam 45, 2022)
After earthquake and tsunami in 2004, Aceh Barat Regency had been trying to reduce disaster risk by making evacuation routes for residents from disaster-prone areas to high and safe places. However, currently several existing evacuation routes are in a badly damaged condition, namely the Alue Peunyareng - UTD Ujong Tanoh Darat Village, Meureubo District and the Meulaboh - Tutut Keuramat Village, Kaway XVI District. If the condition of the road is in a badly damaged condition, during the disaster evacuation process, this area will experience many obstacles, i.e., the level of driving safety and slower vehicle travel time. This study aims to evaluate the level of road damage on the two existing roads by comparing the Bina Marga and Pavement Condition Index (PCI) methods. The data was collected by field observations through measuring the level of damage, and the Average Daily Traffic (LHR) survey. The analysis results by two methods showed that the condition of the Alue Peunyareng - UTD road, Ujong Tanoh Darat Village, Meureubo District was very poor category with an average PCI value of 23.30 and the priority value of handling is 4 with periodic maintenance recommendation, whereas the Meulaboh road - Tutut Keuramat Village, Kaway XVI District was poor category with an average PCI value of 31.33 and a priority value of 3 with road improvement recommendation. The recommendation for alternative treatment is to replace the pavement by calculating the additional pavement layer thickness or by recycling the existing pavement for a more efficient cost.